The Magnesium Concentration in Yeast Extracts Is a Major Determinant Affecting Ethanol Fermentation Performance of Zymomonas mobilis - Li, Runxia; Jin, Mingjie; Du, Jun; Li, Mian; Chen, Shouwen; Yang, Shihui (Frontiers in Bioengineering and Biotechnology, 2020)
Zymomonas mobilis is a model ethanologenic bacterium for diverse biochemical production. Rich medium (RM) is a complex medium that is routinely used to cultivate Z. mobilis, which contains carbon sources such as glucose, nitrogen sources such as yeast extract (YE), and KH2PO4. Glucose consumption and cell growth of Z. mobilis is usually coupled during ethanol fermentation. However, sometimes glucose was not consumed during the exponential growth phase, and it took extended time for cells to consume glucose and produce ethanol, which eventually reduced the ethanol productivity. In this study, the effects of different nitrogen sources, as well as the supplementation of an additional nitrogen source into RM and minimal medium (MM), on cell growth and glucose consumption of Z. mobilis were investigated to understand the uncoupled cell growth and glucose consumption. Our results indicated that nitrogen sources such as YE from different companies affected cell growth, glucose utilization, and ethanol production. We also quantified the concentrations of major ion elements in different nitrogen sources using the quantitative analytic approach of Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES), and demonstrated that magnesium ion in the media affected cell growth, glucose consumption, and ethanol production. The effect of magnesium on gene expression was further investigated using RNA-Seq transcriptomics. Our results indicated that the lack of Mg2+ triggered stress responses, and the expression of genes involved in energy metabolism was reduced. Our work thus demonstrated that Mg2+concentration in nitrogen sources is essential for vigorous cell growth and ethanol fermentation, and the difference of Mg2+concentration in different YE is one of the major factors affecting the coupled cell growth, glucose consumption and ethanol fermentation in Z. mobilis. We also revealed that genes responsive for Mg2+ deficiency in the medium were majorly related to stress responses and energy conservation. The importance of magnesium on cell growth and ethanol fermentation suggests that metal ions should become one of the parameters for monitoring the quality of commercial nitrogen sources and optimizing microbial culture medium.